A new Λ- nucleus potential for the Λ- particle energies in hypernuclei - Efthimiou, C. A.; Grypeos, M. E.; Koutroulos, C. G.; Petridou, Th. (HNPS Advances in Nuclear Physics, 2020)
A new single particle Λ− nucleus potential is considered for the study of the Λ−particle energies in hypernuclei. This potential belongs to the class of potentials for which the formalism of the s−power series expansions of the Hypervirial Theorems technique is applicable. The numbers d_k (k = 0, 1, 2, 3, 4) related to the derivatives of the potential form factor f , determining the potential shape, are obtained and therefore the approximate analytic expression of the energy level Enl (including third-order terms in the small parameter s). Preliminary numerical results are also given and a discussion is made.